2018
DOI: 10.1177/0969733018803662
|View full text |Cite
|
Sign up to set email alerts
|

Ethical decision-making levels of oncology nurses

Abstract: Aim: This study was carried out in order to determine ethical decision-making levels of oncology nurses. Ethical Consideration: Research Ethics Committee's approval was obtained prior to the data collection. Permission to use the Turkish version of the Nursing Dilemma Test was received from Birgül Cerit. Written approval was taken from school administrators to conduct the study confirming that there were no invasive procedures planned for human beings during the study period. The study was conducted in accorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
7
2
3
Order By: Relevance
“…There are many obstacles in informing patients about their cancer, and this is a stressor for medical staff (Ehsani et al, 2016). Another study has shown that it is challenging for oncology nurses to inform patients about their diseases or treatment procedure (Baysal et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are many obstacles in informing patients about their cancer, and this is a stressor for medical staff (Ehsani et al, 2016). Another study has shown that it is challenging for oncology nurses to inform patients about their diseases or treatment procedure (Baysal et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde farklı birimlerde çalışan hemşirelerle yapılmış çalışma sonuçları karşılaştırıldığında birbirinden farklı sonuçlar elde edildiği görülmektedir. Bazı çalışmalarda bu çalışmadakine yakın sonuçlar elde edilmişken (1,17,(25)(26)(27)(28)(29)(30) bazı çalışmalarda hemşirelerin İD düzeyi bu çalışmadaki yoğun bakım hemşirelerinin İD düzeyinden daha yüksek (9,(31)(32)(33)(34), bazı araştırmalarda ise daha düşük belirlenmiştir (35)(36)(37). Araştırma sonuçlarının farklılık göstermesinde, katılımcıların farklı ülkelerde, kurumlarda ve birimlerde görev yapması, karar vermeye yol gösteren rehberlerin kullanımı, eğitim ve otonomi düzeyinin etkili olabileceği düşünülmektedir.…”
Section: Tablo 3 Hemşirelerin Hemşirelik Etik İkilem Testi'nden Aldığı İlkesel Düşünme Ve Pratik Düşünme Puan Ortalamasıunclassified
“…Araştırmada yoğun bakım hemşirelerinin etik sorunlara ilişkin karar verirken, çevresel faktörleri ortalamanın üzerinde önemsedikleri belirlenmiştir. Literatürde farklı birimlerde çalışan hemşirelerle yapılan araştırma sonuçları incelendiğinde, çoğu çalışmada bu çalışmadakine benzer sonuçlar elde edilmişken (1,9,17,25,27,29,33) bazı çalışmaların ise farklılık gösterdiği (26,32,34,35) tespit edilmiştir. Araştırma sonuçlarının tutarsızlık göstermesinde, çalışmaların farklı ülkelerde gerçekleştirilmiş olması, katılımcıların farklı birimlerde çalışması, ekip işbirliği ve görev tanımlarına ilişkin algı, yönetici desteği, kurumsal prosedür ve politikaların yansımalarının olabileceği söylenebilir.…”
Section: Tablo 4 Hemşirelerin Ahlaki Duyarlılığı Ile Etik Karar Verebilme Düzeyi Arasındaki Korelasyon Analiziunclassified
“…4 Due to the complexity of these challenges and their potential to result in conflict, 11 it is important for nurses to be aware of these ethical challenges and to develop their ethical decision-making skills to better tackle these challenges. 13 In this regard, it is imperative that nurses have a detailed understanding of the ethical challenges and are able to use strategies to meet them. 14 Correct ethical decisions by nurses may improve the patient’s recovery and the quality of healthcare services, and reduce healthcare costs.…”
Section: Introductionmentioning
confidence: 99%
“…14 Correct ethical decisions by nurses may improve the patient’s recovery and the quality of healthcare services, and reduce healthcare costs. 13…”
Section: Introductionmentioning
confidence: 99%